Quantifying conflict zones as a challenge to certification of Guinea worm eradication in Africa: a new analytical approach - Louise A Kelly-Hope; David H Molyneux (BMJ Open, 2021)
Objectives To quantify conflict events and access across countries that remain to be certified free of transmission of Dracunculus medinensis (Guinea worm disease) or require postcertification surveillance as part of the Guinea Worm Eradication Programme (GWEP).Setting and participants Populations living in Guinea worm affected areas across seven precertification countries and 13 postcertification sub-Saharan African countries.Outcome measures The number of conflict events and rates per 100 000 population, the main types of conflict and actors reported to be responsible for events were summarised and mapped across all countries. Chad and Mali were presented as case studies. Guinea worm information was based on GWEP reports. Conflict data were obtained from the Armed Conflict Location and Event Data Project. Maps were created using ArcGIS V.10.7 and access was measured as regional distance and time to cities.Results More than 980 000 conflict events were reported between 2000 and 2020, with a significant increase since 2018. The highest number and rates were reported in precertification Mali (n=2556; 13.0 per 100 000), South Sudan (n=2143; 19.4), Democratic Republic of Congo (n=7016; 8.1) and postcertification Nigeria (n=6903; 3.4), Central Africa Republic (n=1251; 26.4), Burkina Faso (n=2004; 9.7). Violence against civilians, protests and battles were most frequently reported with several different actors involved including Unidentified Armed Groups and Boko Haram. Chad and Mali had contracting epidemiological and conflict situations with affected regions up to 700 km from the capital or 10 hours to the nearest city.Conclusions Understanding the spatial–temporal patterns of conflict events, identifying hotspots, the actors responsible and their sphere of influence is critical for the GWEP and other public health programmes to develop practical risk assessments, deliver essential health interventions, implement innovative surveillance, determine certification and meet the goals of eradication.